Perbandingan Hasil Kelentikan Bulu Mata Menggunakan Penjepit Bulu Mata Dan Maskara Pada Rias Wajah Pagi - Nurcahyati Nurcahyati; Mitra Lusiana (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
The need for practical, efficient, and long-lasting makeup is increasing, especially among women who are active in daily activities such as work, college, and social activities. One important element in creating a fresh, expressive, and attractive facial appearance is the condition of the eyelashes. Curled eyelashes can give the impression of larger, fresher, and more vibrant eyes. In makeup practice, there are various ways to curl eyelashes, including using eyelash curlers and mascara. Eyelash curlers are known to provide instant results with a noticeable curling effect, but they are often less durable and have the risk of damaging eyelashes if not used properly. Conversely, using mascara alone is considered more practical and safe, but often less than optimal, especially for individuals with short or straight eyelashes. This study aims to compare the results of eyelash curl and durability between the use of a conventional eyelash curler combined with mascara and the use of mascara alone in morning makeup. The research method used was a quantitative experiment with a One Shoot Case Study design. The research subjects consisted of six female students of the Makeup and Beauty Study Program, Padang State University, who were selected using a purposive sampling technique. Two treatment groups were formed, each receiving a different makeup technique. Seven panelists assessed the curl and durability of the eyelash makeup throughout the day through direct observation and photographic documentation. The results showed that the combination of using an eyelash curler and mascara provided significantly better curl and durability than mascara alone. A t-test confirmed a significant difference in curl (p = 0.001) and durability (p = 0.003). Based on these findings, it can be concluded that the combination of an eyelash curler and mascara is recommended for users who desire maximum, fresh, and long-lasting morning makeup results throughout their daily activities.